Suppression of neovascularization in corneal stroma in a TRPA1-null mouse. (April 2019) - Usui-Kusumoto, Keiko; Iwanishi, Hiroki; Ichikawa, Kana; Okada, Yuka; Sumioka, Takayoshi; Miyajima, Masayasu; Liu, Chia-Yang; Reinach, Peter S.; Saika, Shizuya
Abstract: Corneal neovascularization and inflammatory fibrosis induced by severe injury or infection leads to tissue opacification and even blindness. Transient receptor potential (TRP) channel subtypes contribute to mediating these maladaptive responses through their interactions with other receptors. TRPV1 is one of the contributing channel isoforms inducing neovascularization in an alkali burn mouse wound healing model. VEGF-A upregulation contributes to neovascularization through interaction with its cognate receptors (VEGFR). Since the TRP isoform in this tissue, TRPA1, is also involved, we determined here if one of the pathways mediating neovascularization and immune cell infiltration involve an interaction between VEGFR and TRPA1 in a cauterization corneal mouse wound healing model. Localization of TRPA1 and endothelial cell (EC) CD31 immunostaining pattern intensity determined if TRPA1 expression was EC delimited during cauterization induced angiogenesis. Quantitative RT-PCR evaluated the effects of the absence of TRPA1 function on VEGF-A and TGF-β1 mRNA expression during this process. Macrophage infiltration increased based on rises in F4/80 antigen immunoreactivity. TRPA1 immunostaining was absent on CD31-immunostained EC cells undergoing neovascularization, but it was present on other cell type(s) adhering to EC in vivo. Absence of TRPA1 expression suppressed both stromal neovascularization and inhibited macrophage infiltration. Similarly, the increases occurring in both VEGF-A and TGF-β1 mRNA expression levels in WT tissue were blunted in the TRPA1 −/− counterpart. On the other hand, in the macrophages their levels were invariant and their infiltration was inhibited. To determine if promotion by TRPA1 of angiogenesis was dependent on its expression on other unidentified cell types, the effects were compared of pharmacological manipulation of TRPA1 activity on EC proliferation tube formation and migration. In the presence and absence of a fibroblast containing feeder layer. Neither VEGF-induced increases in human vascular endothelial cell (HUVEC) proliferation nor migration were changed by a TRPA1 antagonist HC-030031 in the absence of a feeder layer. However, on a fibroblast feeder layer this antagonist suppressed HUVEC tube formation. In conclusion, during corneal wound healing transactivation by VEGFR of TRPA1 contributes to mediating neovascularization and macrophage infiltration. Such crosstalk is possible because of close proximity between VEGFR delimited expression on EC and TRPA1 expression restricted to cell types adhering to EC. Highlights: Corneal avascularity contributes to preserving corneal transparency and normal vision. In a mouse corneal injury wound healing model, alkali exposure induces excessive transient increases in VEGF-A gene and protein expression levels that activate its cognate receptor, VEGFR. Targeting corneal TRPA1 signaling activation induced by injury may in turn inhibit VEGF-induced neovascularization. Such an outcome has the potential to provide an alternative therapeutic option to reduce losses in visual acuity and hasten functional recovery of corneal transparency during the wound healing process.